If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6r + -3)(8r + -3) = 0 Reorder the terms: (-3 + 6r)(8r + -3) = 0 Reorder the terms: (-3 + 6r)(-3 + 8r) = 0 Multiply (-3 + 6r) * (-3 + 8r) (-3(-3 + 8r) + 6r * (-3 + 8r)) = 0 ((-3 * -3 + 8r * -3) + 6r * (-3 + 8r)) = 0 ((9 + -24r) + 6r * (-3 + 8r)) = 0 (9 + -24r + (-3 * 6r + 8r * 6r)) = 0 (9 + -24r + (-18r + 48r2)) = 0 Combine like terms: -24r + -18r = -42r (9 + -42r + 48r2) = 0 Solving 9 + -42r + 48r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '3'. 3(3 + -14r + 16r2) = 0 Factor a trinomial. 3((3 + -8r)(1 + -2r)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(3 + -8r)' equal to zero and attempt to solve: Simplifying 3 + -8r = 0 Solving 3 + -8r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -8r = 0 + -3 -8r = 0 + -3 Combine like terms: 0 + -3 = -3 -8r = -3 Divide each side by '-8'. r = 0.375 Simplifying r = 0.375Subproblem 2
Set the factor '(1 + -2r)' equal to zero and attempt to solve: Simplifying 1 + -2r = 0 Solving 1 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2r = 0 + -1 -2r = 0 + -1 Combine like terms: 0 + -1 = -1 -2r = -1 Divide each side by '-2'. r = 0.5 Simplifying r = 0.5Solution
r = {0.375, 0.5}
| x-7=2x-3 | | 13+3x-9=10x-14-5x | | -9=108 | | 3x^2-3=45 | | x^2-24x+1=0 | | 100(x-3)=450-50 | | t/3-2=9 | | -6(8+6k)=-228 | | 7/5(40) | | x+7/5x=96 | | 6d/4=24 | | -153-12x=71+2x | | -5+7=5x-4(x-1) | | 9Y-1=y-5 | | D(3-7)-12=0 | | 6m/7-3=9 | | -82-3x=11x+170 | | 7m-10m=27 | | .5=.09 | | 9(w-4)=7w-44 | | 3+573g=3g | | 3+573=3g | | 3m^3-32m-8=0 | | 3+573=g | | 3a+3a=16+18a | | an=-7+6 | | -98-3x=98-10x | | .66t+4=2 | | 4096=r^6 | | 2x+5y=-34 | | t=96t-16t^2 | | l=5+2x |